Aprendizagens docentes situadas em uma comunidade de prática constituida a partir do OBEDUC - Tinti, Douglas da Silva (2016)
This research has aimed to identify and describe some teacher’s learnings evidenced in a Community of Practice (CoP OBEDUC PUC-SP) to evaluate and discuss elements of the context of this CoP that revealed/allowed those learning. It concerns to a study based on qualitative aspect, kind of participating research (GIL, 2002). The data have been gotten from June, 2013 to July, 2015 through recordings and productions of the members that integrated the CoP, added to diaries of descriptions from the researchers. To evaluate them, we consider the perspective of the Learning Theory (LAVE; WENGER, 1991), which indicates that all the activities (including learning) takes place into the relations of people, contexts and practices. Considering that a CoP can pass by different stages into its developing process (WENGER et al., 2002), the organization of these data has been structured, by considering the Potential Steps, the Expansion and Maturity. After listening to the recording, we’ve done a descriptive-analytic evaluation of each one of these Stages to answer the following: what kind of different teaching learnings have been evidenced in stages of development of a CoP, constituted by a project OBEDUC PUC-SP? Among the evidenced teaching learning, we’ve pointed: the writing reports and the reflection on the own practices; the construction of conceptual maps; the constitution and belonging to a CoP; how to deal with a diversity of profiles and trajectories into a CoP; the individual and collective activities development, involvement of a perspective to problem resolutions; the study and handle with manipulating materials especially concerning to fractional numbers. We’ve concluded that teaching learnings accomplished during the stages of the OBEDUC PUC-SP CoP development have been multiples and converge to the Knowledge of/to/in practice proposed by Cochran-Smith e Lytle (2009)